Web-Based Document Workflow Management Information System - Emny Harna Yossy; Yohan Aris Darmawan (LPPM Universitas Islam 45 Bekasi, 2023)
In business process and document approval characteristics, approval workflow is a process for automatically flowing business between approval providers with predetermined rules. When viewed from the process of requesting goods still uses e-mail. With the increasing number of documents that must be approved and still using e-mail communication media, obstacles were found that caused delays in the document approval process. In this study, the authors aim to create a computerized workflow document, which will be implemented in the procedure for purchasing requests for goods and requests for promotional items from branches and assisting document recipients in sorting out documents that have not/have been approved which are expected to provide benefits to users in carrying out the process. Document approval. The information system the author has developed can only be run for internal users who already have login access to the system and can only be accessed using the internal network. The development process uses the waterfall method, and data collection methods in this study include observation, interviews, and literature study. System testing is carried out using blackbox testing evaluation and interface design evaluation using the eight golden rules. From the implementation and evaluation results, it was concluded that the system had achieved the desired results, namely, the branch admin page for sending information on approval documents and the approval party page for responding to documents.